Video documental biográfico sobre Paco Salvador. - Pérez Lascano, José David (2016)
The following text will present an audiovisual recording about the Paco Salvador’s biography, thanks to this; it will be possible that choreographers and dancers realize that is really important a deep research before to make a performance. Paco Salvador, a very important ecuadorian person, who has a Master’s degree in Studies about Culture and with a great CV, does extensive research for performing their choreographies. He has an interesting proposal which consist in to name popular dance, to a kind of dancing that respect the original essence of a culture. Its a fact that none tradition must be static, but it has to have a dinamism and different changes and evolutions. It show the popular dancing concept with the Muyacan group, which is the director and coreographer. In Ecuador there is not a culture of research about dancing topics, for that reason, choreographers and dancers just follow a unique idea, without spend time in a true exploration. These kind of situations over and over repeated, cause folkloric practices, distorting the real ecuadorian culture and locate them in a completely different context. In addition, it is necessary decline the idea of the most of the dance groups in Ecuador; about that indigenous culture is the unique that can represent our identity. Paco Salvador lived in a context full of history, in a small Ibarra and in a Ecuador full of prejudices and discrimination, where his question about the world and art were present since he was very Young, it causes that he decide for the more complete mode of expresión corporal, dancing.